COMPARISON OF THE INCIDENCE OF DEMENTIA IN PATIENTS WITH TYPE 2 DIABETES MELLITUS AND NON TYPE 2 DIABETES MELLITUS - Vincentia Vania Satya; Yudita Wulandari; Tabita Novita Anggriani (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2023)
Background : Diabetes melitus is a risk factor for dementia. People often assume that memory impairment or memory loss is a normal symptom or a normal process. Therefore, there is a lack of treatment for dementia in the community. Early detection needs to be done to determine the presence of dementia in patients with type 2 diabetes melitus and non diabetes melitus type 2. Purpose : To determine the incidence of dementia in patients with type 2 diabetes melitus compared to patients with non diabetes melitus type 2. Method : The research design used in this research is observational analytic, with the research design used is cross sectional. The sampling technique used is probability sampling with simple random sampling. Selecting population members based on predetermined inclusion and exclusion criteria. With a sample of 58 people in the control group and 58 people in the case group. Result : Samples were collected using secondary data obtained from medical records of patients with dementia at Abdoel Wahab Sjahranie Samarinda Hospital during the 2019-2021 period. The results of the study showed that 54 people (46,6%) developed dementia, of them with type 2 diabetes melitus as many as 39 people, while non-diabetes melitus type 2 as many as 15 people. Respondents without dementia were 62 people (53.4%), of them with type 2 diabetes melitus as many as 19 people, while non-diabetes melitus type 2 as many as 43 people. There was a significant difference in the incidence of dementia in patients with type 2 diabetes melitus and non diabetes melitus type 2 (p = 0.000).Conclusion : There is a significant difference in the incidence of dementia in patients with type 2 diabetes melitus and non diabetes melitus type 2. Keyword : Dementia, Type 2 Diabetes Melitus